Wendy : The Bumper Book of Fun for Women of a Certain Age - Eclair, Jenny and Holder, Judith (London Hodder & Stoughton, 2008)
From the creators of Grumpy Old Women comes a hilarious, irreverent and beautifully designed ode to the joys, angers, desires and embarrassments of middle-aged women
Include Color Illustration
Keywords: Middle-aged women